Identifying Key Features of the Innovated Japanese Project Management: A Critical Review on its Philosophy - Low, F.; Chong, Heap Yih; Lee, W. (ET Pub, 2013)
Project management is an important skill that determines the success or failure of a project. The Japanese project management (JPM) methods, namely Project and Program Management (P2M) and Kaikaku Project Management (KPM), are innovated project management methodologies that have been proven to be effective. This paper presents a critical review of its key features and elements in terms of its philosophy, management tools and project models. The research findings will eventually bring awareness and provoke interest in organizations worldwide to implement or apply the methods if found to be suitable in their project management processes.